Sufism : An Introduction to the Mystical Tradition of Islam - Ernst, Carl W. (Boston Shambhala, 2011)
The soaring voice of Nusrat Fateh Ali Khan, the ecstatic dance of the Whirling Dervishes, the rapturous verse of Jalaluddin Rumi$1 (Ball are expressions of Sufism, often regarded as the mystical tradition of Islam. Who are the Sufis? They are more than mystics; they are empowered by the Qur'an and the Prophet Muhammad. They are guided by saints and masters. They belong to orders ranging from North Africa and Turkey to India and Central Asia. In addition to prayer and fasting, they practice techniques of meditation. They recite poetry, delight in music, and perform dance, all towards one goal$1 (Bunion with God, the Divine Beloved. This comprehensive introduction clarifies the concept of Sufism and discusses its origin and development. In addition, the author discusses the important issues of Sufism's relationship with the larger Islamic world and its encounters with fundamentalism and modern secularism, along with the appropriation of Sufism by non-Muslims and the development of Sufi traditions in the West.s
Include Figures, Notes, Bibliography, Discography and Index.
An Introduction to the Mystical Tradition of Islam.
Keywords: Sufism -- Mysticism--Islam